Debating wine health-warning labels using Q methodology - Francesco Solfanelli; Serena Mandolesi; Ileana Silvestri; Simona Naspetti; Raffaele Zanoli (Wine Economics and Policy, 2025)
In Europe, alcohol-related diseases have an increasingly high impact on healthcare costs every year. Hence, rising consumer consciousness regarding the risks and harms of drinking alcohol is a primary goal of the EU Commission. Recently, the Commission has been discussing the mandatory adoption of health-warning labels (HWLs) on all alcoholic beverages, including wine. This study investigated expert and non-expert perceptions of adopting health-warning labels on wine bottles. The research used Q methodology, a mixed-method approach to explore subjective viewpoints regarding adopting health-warning labels for the wine sector. Respondents were evenly distributed among wine experts and consumers. The results provided four different views based on participants’ perceptions of HWLs. Factor 1 (the “Nationalism” view) strongly opposes the proposal, which is considered extremely dangerous for the entire wine market. Factor 2 (the “Market-oriented” view) believes that health warnings will increase transparency in the market and help consumers make informed choices, thereby respecting consumer autonomy. Factor 3 (the “Health-first” view) strongly believes that informing consumers through health labels on all alcoholic beverages is necessary to protect public health. Lastly, Factor 4 (the “Keep Us Alive” view) underestimates warning labels’ effectiveness in promoting the right behaviours. The findings highlight different “sides” of this debating topic and provide valuable insight into how policymakers can investigate new strategies, always considering and respecting consumer choice.